FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILAHAN SAMPAH DI PASAR SAIL KECAMATAN SAIL KOTA PEKANBARU TAHUN 2017 - Alhidayati; Leon Candra (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2020)
Garbage is the rest of the daily activities of humans or natural processes in the form of solid. Specific waste is waste which due to its nature, concentration, or volume requires special management. The source of waste is the origin of waste dump. Variables to be studied have an influence on the separation of waste variables in the form of knowledge, attitude, action, socialization, and facilities. The method used in this research is quantitative with cross sectional study design. The purpose of this research is to know the factors that influence waste segregation in Sail market, Sail Sub-district, Pekanbaru City in 2017. The result of research is knowledge relation with waste selection with P = 0,009 OR = 5,11 (95% CI = 1,624- 16,083). There is a relationship of attitude with the selection of waste with the value of P = 0.017 OR = 4,463 (95% CI = 1,444-13,792), there is a correlation of action with waste selection with P value = 0.010 OR = 5,143 (95% CI = 1,610-16,430) , there is a socialization relationship with the selection of waste with the value of P = 0.022 OR = 4,364 (95% CI = 1,376-13,841), and there is a correlation of means with the selection of waste with value P = 0,001 OR = 7,393 (95% CI = 2,255- 24,232). Therefore, this study can be concluded that the variables of knowledge, attitude, action, socialization and facilities are very influential on the sorting of waste in Sail Market Pekanbaru City in 2017.